Development and innovation of electronic systems in an automobile: a review - Noroña, Marco; Gómez, Manuel (Enfoque UTE, 2019)
This article presents a study of the technological advances in the electronic part of an automobile, based on an analysis of the technical, economic, productive and environmental specifications considered in the design, development and innovation of components of a vehicle that meet the requirements of the automotive companies. It systematically explains the idea and content of the innovation systems implemented in vehicles in recent years, in the electrical-electronic part, after several studies carried out by scientists, researchers and innovation analysts in the field of automotive electronics. The transformations occurred in the last years in the electrical-electronic part of a vehicle are discussed and a comparative analysis of the modifications and / or improvements in the characteristics of the automotive systems is elaborated, in order to comply with the existing regulations regarding energy consumption. , performance, waste treatment, comfort, safety, among others. The introduction of new sensors, control units and actuators, related to microelectronics, telematics and multimedia to vehicles, provides profound changes in the design, production, operation and diagnosis of a car, which have been gradually implemented in the systems of brakes , transmission, steering, safety, comfort and engine.